(untitled) (Architecture Image Studies, 2025)
Effective writing skill is a very powerful weapon in the armoury of any decently educated person. So, more often than not, students and a sizable section of a society of any country always aimed at writing better in order to make a mark in their own respective fields not to talk of the literary fraternity who not only dedicated their lives to literary exploits but also earned a place in the select club of ace writers – all with whatever resources they had in their time. Of course, the one common thread that ran through all these people is that they all wanted to better their writing skills all the time – some aimed at making better drafts while others focused in creating literary masterpieces. Interestingly enough, Artificial Intelligence, these days, ranks high if the objective is to become better in communication skills – written or oral. It offers students dynamic support all the time across idea generation, drafting and revision. The study aims to explore the role of generative AI technologies in enhancing the writing process across its core stages: idea generation, drafting and revision. It examines the different phases of interaction with Chat GPT models in terms of evolution of Chat GPT from its earliest versions to the latest versions. Their features critically evaluate how AI tools assist students in developing writing skills. The study investigates the evolution and matured levels of AI powered writing through successive versions of Open AI‘s language models- from GPT -2 (2019) to the current GPT- 4 turbo and how each stage has contributed to the development of students writing and composition skills. The novelty of the research is that how improvements in each version correlate with different cognitive and linguistic outcomes and how each version is mapped on to with the much anticipated educational outcomes. By and large, this approach offers a new framework for educators and researchers to evaluate AI’s use in the writing instruction covering not just the technical viewpoint but also the pedagogical perspectives per se.